Determination of the discharge coefficient of a heavy hydraulic head slide gate - Salvador Rojas, Bernardino (2020)
The results of a field and office study to determine the discharge coefficient (Cd) of a "sluice gate" of a water storage and intake system of a hydropower project are reported. In most hydropower projects, water is withdrawn from a dam built on a riverbed. Downstream of the dam the living conditions in the river are altered. To remedy this situation, mainly in times of low water, water is released from the dam in a controlled manner (ecological flow), usually by operating the sluice gate. In this context, the problem of the reservoir operators is related to the opening of the sluice gate that guarantees the ecological flow for a given level of the water in the reservoir. To solve this problem, the discharge downstream of the gate was measured for 3 gate relative openings (5%, 10% and 15%) and different water levels in the reservoir. With these data Cd values were found. The results show that tends to increase for openings smaller than 15%. This tendency could be influenced by the geometry of the lower lip of the gate.